Effects of phosphate loading on metabolic and myocardial responses to maximal and endurance exercise - Kreider, R. B.; Miller, G. W.; Schenck, D.; Cortes, C. W.; Miriel, V.; Somma, C. T.; Rowland, P.; Turner, C.; Hill, D. (International Journal of Sport Nutrition and Exercise Metabolism, 1992)
Six trained male cyclists and triathletes participated in a double blind study to determine the effects of phosphate loading on maximal and endurance exercise performance. Subjects ingested either 1 gm of tribasic sodium phosphate or a glucose placebo four times daily for 3 days prior to performing either an incremental maximal cycling test or a simulated 40-km time trial on a computerized race simulator. They continued the supplementation protocol for an additional day and then performed the remaining maximal or performance exercise test. Subjects observed a 17-day washout period between testing sessions and repeated the experiment with the alternate supplement regimen in identical fashion. Metabolic data were collected at 15-sec intervals while venous blood samples and 2D-echocardiographic data were collected during each stage of exercise during the maximal exercise test and at 8-km intervals during the 40-km time trial. Results indicate that phosphate loading attenuated anaerobic threshold, increased myocardial ejection fraction and fractional shortening, increased maximal oxidative capacity, and enhanced endurance performance in competitive cyclists and triathletes.